Prognostic value of neutrophil gelatinase-associated lipocalin and glycosylated hemoglobin for non-ST-segment elevation myocardial infarction patients with single concomitant chronic total occlusion following primary percutaneous coronary intervention: A prospective observational study. Issue 39 (September 2019) - Peng, Wenhua; Zhang, Channa; Wang, Zhijun; Yang, Wenqi; Luo, He; Li, Xiaofeng; Fu, Dongliang; Yu, Changan; Zhou, Yifeng
Abstract : Abstract: To investigate factors predicting the onset of major adverse cardiovascular and cerebrovascular events (MACCEs) after primary percutaneous coronary intervention (pPCI) for patients with non-ST-segment elevation infarction (NSTEMI) and single concomitant chronic total occlusion (CTO). Neutrophil gelatinase-associated lipocalin (NGAL) and glycosylated hemoglobin (HbA1c) both play essential role in cardiovascular and cerebrovascular homoeostasis. However, current knowledge of its predictive prognostic value is limited. 422 patients with NSTEMI and CTO (59.7 ± 12.4 years, 74.2% men) who underwent successful pPCI were enrolled and followed for 2 years. Multivariate cox regression analysis and receiver operating characteristic (ROC) curve analysis were performed to determine the factors predicting MACCEs. 140 patients (33.2%) experienced MACCEs in the follow-up period. Multivariate cox regression analysis found when we process the model with NGAL at admission, low left ventricular ejection fraction (LVEF, HR = 0.963, 95% CI 0.940 to 0.987, P = .003) and fasting blood glucose (HR = 1.078, 95% CI 1.002 to 1.159, P = .044), but not NGAL at admission, were independent predictors of 2 years MACCEs. While HbA1C (HR = 1.119, 95% CI 1.014 to 1.234, P = .025), LVEF (HR = 0.963, 95% CI 0.939 to 0.987, P = .003), estimated glomerular filtration rate (HR = 1.020, 95% CI 1.006 to 1.035, P = .006) and NGAL value 7 day (HR = 1.020, 95% CI 1.006 to 1.035, P = .006) showed their predictive value in another model. ROC analysis indicated NGAL 7 day (AUC = 0.680, P = .0054 and AUC = 0.622, P = .0005) and LVEF (AUC = 0.691, P = .0298 and AUC = 0.605, P = .0021) could predict both in-hospital and 2 years MACCEs, while higher NGAL at admission could only predict poorer in-hospital prognosis (AUC = 0.665, P = .0103). Further analysis showed the prognostic value of NGAL was particularly remarkable among those HbA1C<6.5%. Patients with NSTEMI and single concomitant CTO receiving pPCI with higher NGAL on 7 days during hospitalization are more likely to suffer 2 years MACCEs, particularly in those with lower HbA1C.